Cadeias de valor baseadas em recursos naturais: O caso do Brasil - Pedro Luiz da Motta Veiga; Sandra Polónia Rios (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This article analyzes, for the case of Brazil, the structure and the dynamics of two natural resources-based value chains: the poultry and wood furniture chains. The study shows that, in the sectors analyzed, there exist different models of organization of the value chains. Those differences are one of the factors accounting for the performance of the Brazilian firms in the value chains they participate, as well as the possibilities of upgrade of the firms within these chains.
Keywords: F15; F63; L22; L23; L52; 330; economic integration; economic development; firm organization and market structure; organization of production; industrial policy